Figurações do tardio no último Herberto Helder - Roberto Bezerra de Menezes (2018)
Understanding the notion of late style as a research proposition that must necessarily develop with the approach of the case under analysis, not as a mere detached proposition of artistic achievement and that which produced it, very similar to what was practiced by Edward Said, without dispensing with what is presented as difference and uniqueness, the research we are looking for identifies traces of a late style (ADORNO,2002; SAID, 2009) and/or manner (AGAMBEN, 2011) in the last poem by Herberto Helder, more specifically the from the publication of A faca não corta o fogo: súmula & inédita (2008), paying special attention to the changes in its poetics resulting from the confrontation with the proximity of death, revealed the awareness of finitude.